Wheat gene bank accessions as a source of new alleles of the powdery mildew resistance gene Pm3: a large scale allele mining project - Bhullar, Navreet K (BioMed Central, 2010)
BACKGROUND: In the last hundred years, the development of improved wheat cultivars has led to the replacement of landraces and traditional varieties by modern cultivars. This has resulted in a decline in the genetic diversity of agriculturally used wheat. However, the diversity lost in the elite material is somewhat preserved in crop gene banks. Therefore, the gene bank accessions provide the basis for genetic improvement of crops for specific traits and and represent rich sources of novel allelic variation. RESULTS: We have undertaken large scale molecular allele mining to isolate new alleles of the powdery mildew resistance gene Pm3 from wheat gene bank accessions. The search for new Pm3 alleles was carried out on a geographically diverse set of 733 wheat accessions originating from 20 countries. Pm3 specific molecular tools as well as classical pathogenicity tests were used to characterize the accessions. Two new functional Pm3 alleles were identified out of the eight newly cloned Pm3 sequences. These new resistance alleles were isolated from accessions from China and Nepal. Thus, the repertoire of functional Pm3 alleles now includes 17 genes, making it one of the largest allelic series of plant resistance genes. The combined information on resistant and susceptible Pm3 sequences will allow to study molecular function and specificity of functional Pm3 alleles. CONCLUSIONS: This study demonstrates that molecular allele mining on geographically defined accessions is a useful strategy to rapidly characterize the diversity of gene bank accessions at a specific genetic locus of agronomical importance. The identified wheat accessions with new resistance specificities can be used for marker-assisted transfer of the Pm3 alleles to modern wheat lines.